THE CORRELATION OF MOTHER'S AGE AT MARRIAGE AND MOTHER'S WORK STATUS WITH EXCLUSIVE BREASTFEEDING - Lina Juhaidah (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
The best nutrition for babies is breast milk. Breast milk should be given exclusively without any additions in the first six months. According to previous research, a woman’s age at marriage will affect the practice of exclusive breastfeeding to their babies, as young mothers are often not ready to have and care for babies. The work status of mothers also has a large impact on exclusive breastfeeding practices. The goal of this study was to discover the correlation between age at marriage and the work status of mothers with exclusive breastfeeding practices. This research was an observational study with the subjects being 94 mothers of children aged 0-5 years in Ngringinrejo Village, Kalitidu District, Bojonegoro Regency from 3 July to 9 August, 2019. This study used data from the professional placement activity or Praktik Kerja Lapangan (PKL) conducted by the students of the public health study program of Airlangga University. The outcome of this research showed that there was no meaningful relationship between the age of marriage of mothers and practices of exclusive breastfeeding (p-value = 0.973) and there is also no statistical relationship between the work status of mothers and exclusive breastfeeding practices (p-value = 0.276). However, it was discovered that mothers who gave exclusive breastfeeding were mostly not working, and mothers who did not breastfeed exclusively were mostly in employment. The conclusion of this research is the absence of a correlation between age at marriage and the work status of mothers with exclusive breastfeeding.